Blended Concessional Finance : Scaling Up Private Investment in Lower-Income Countries - Sierra-Escalante, Kruskaia; Karlin, Arthur; Lauridsen, Morten Lykke (International Finance Corporation, Washington, DC, 2019)
Blending funds from private investors with concessional funds from donors and philanthropic sourceshas a strong potential to scale up investment in lower-income countries and thereby acceleratedevelopment. The use of blended concessional finance is already prevalent in lower-income countriesrepresenting over 70 percent of IFC’s commitments. Recent strategies from development financeinstitutions including the World Bank Group indicate that the relative share of lower-income countries in the global mix of blended concessional finance will increase further. Scaling up engagements in lower-income countries requires solutions tailored to local contexts, as well as the deployment of the whole spectrum of development finance tools, including advisory work, regulatory dialogue and reform, and a mix of blending instruments encompassing both pricing and risk mitigation features.